Considerations in the Design of Materials for Solar‐Driven Fuel Production Using Metal‐Oxide Thermochemical Cycles. Issue 2 (8th October 2013) - Miller, James E.; McDaniel, Anthony H.; Allendorf, Mark D.
<x xml:space="preserve">Abstract</x> With demand for energy increasing worldwide and an ever‐stronger case building for anthropogenic climate change, the need for carbon‐neutral fuels is becoming an imperative. Extensive transportation infrastructure based on liquid hydrocarbon fuels motivates development of processes using solar energy to convert CO2 and H2O to fuel precursors such as synthesis gas. Here, perspectives concerning the use of solar‐driven thermochemical cycles using metal oxides to produce fuel precursors are given and, in particular, the important relationship between reactor design and material selection is discussed. Considering both a detailed thermodynamic analysis and factors such as reaction kinetics, volatility, and phase stability, an integrated analytical approach that facilitates material design is presented. These concepts are illustrated using three oxide materials currently receiving considerable attention: metal‐substituted ferrites, ceria, and doped cerias. Although none of these materials is "ideal, " the tradeoffs made in selecting any one of them are clearly indicated, providing a starting point for assessing the feasibility of alternative materials developed in the future.